Hubungan Pola Makan Dengan Tanda dan Gejala Gastritis Pada Mahasiswa Keperawatan di Universitas Murni Teguh - Juliman Halawa; Hizkianta Sembiring (PT. Hasba Edukasi Mandiri, 2025)
Backgound : Gastritis is an inflammation that occurs in the gastric mucosa which can be acute, chronic, diffuse or local caused by the presence of Helicobacter pylori bacterial infection or the destruction of the protective mucosa of the stomach. Diet is the arrangement and amount of food consumed by an individual or group at a certain time consisting of the frequency of meals, types of food, and portions of meals. Often students usually have a messy meal schedule, often eat late, skip breakfast so that the stomach is empty during long meals, the instant lifestyle is also not good, making students really like to consume fast food and drinks. Objective : To determine the relationship between eating patterns and signs and symptoms of ulcers in for nursing students Murni Teguh university. Method : This type of research is quantitative with a correlational approach. Sampling was taken using purposive sampling as many as 151 respondents. Data analysis used the Spearman rho correlation test. Results : The results of this study show that there is a significant relationship between diet and signs and symptoms of gastritis with a p-value of 0.010 < 0.05 and a correlation coefficient of 0.210. Conclution : There is a relationship between eating patterns and signs and symptoms of gastritis in nursing students in Murni Teguh University. Suggestion: It is recommended to conduct follow-up research with more samples and add stress management variables, intestinal metaplasia in patients with acute and chronic gastritis with the selection of different research methods.